2019
DOI: 10.1007/s11101-019-09614-2
|View full text |Cite
|
Sign up to set email alerts
|

Paulownia C-geranylated flavonoids: their structural variety, biological activity and application prospects

Abstract: Paulownia species, especially their flowers and fruits, are traditionally used in Chinese herbal medicines for the treatment of infectious diseases. Cgeranylated flavonoids were found to be the major special metabolites in Paulownia flowers and fruits, and 76 C-geranylated flavonoids had been isolated and characterized thus far. Structural variations in Paulownia C-geranylated flavonoids are mainly due to the complicated structural modifications in their geranyl substituents. These natural compounds have attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The genus Paulownia has been used as a folk remedy, especially in traditional Chinese medicine, and more recently has been considered an interesting source of secondary metabolites, such as flavonoids, lignans, phenolic acids and terpenoids [ 1 ]. Different parts of the tree (bark, fruit, xylem, and leaves) have shown therapeutic properties, mainly due to antioxidant, anti-inflammatory, antimicrobial and anticancer activities [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Paulownia has been used as a folk remedy, especially in traditional Chinese medicine, and more recently has been considered an interesting source of secondary metabolites, such as flavonoids, lignans, phenolic acids and terpenoids [ 1 ]. Different parts of the tree (bark, fruit, xylem, and leaves) have shown therapeutic properties, mainly due to antioxidant, anti-inflammatory, antimicrobial and anticancer activities [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the phenolic components with antioxidant properties may be responsible for the observed activity in traditionally used bark extracts [ 5 , 6 , 8 , 9 , 10 ], and they can also be used as chemotaxonomic markers [ 6 ]. Antioxidants can protect from the damage caused by free radicals and can protect lipid-containing food and cosmetic stuffs from oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The intense blue bands visible in UV after derivatization (especially at Rf = 0.29 and 0.05, Figure 4C) probably came from flavonoid compounds. The leaves of paulownia contain numerous flavonoids, including luteolin, quercetin, apigenin and their derivatives and wide group of C-geranylated flavonoids [32,48]. Among unidentified compounds, particularly interesting was the band with Rf = 0.22, which glowed red in UV light after p-anisaldehyde derivatization.…”
Section: Hptlc Polyphenolic Profile and Verbascoside Quantificationmentioning
confidence: 99%
“…A total of twelve C-geranylated flavanones were selected to evaluate their antiviral activity against the SARS-CoV papain-like protease (PLpro). A multitude of viral life cycle phases requires protease enzymes [51]. The majority of the isolated compounds are SARS-CoVPLpro inhibitors.…”
Section: C-geranylated Flavonoids (Tomentin A-e)mentioning
confidence: 99%